อุบัติการณ์และปัจจัยเสี่ยงของโรคเบาหวานชนิดที่ 2 ในผู้ใหญ่ที่ติดเชื้อเอชไอวี-1 ที่ได้รับการรักษาด้วยยาต้านไวรัสในประเทศไทย - ประกิต ริยะเทน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study can be claimed as the first report in Thailand which studies about incidence of type 2 diabetes in HIV-1 infected adult patients. This study aimed to estimate an incidence and identify risk factors of diabetes in HIV infected adult patients treated with antiretroviral therapy (ART) in “Observational cohort of HIV infected adults in the PHPT network hospitals in Thailand” (PHPT Cohort) study between 1st January 2000 and 31st December 2011. Patients who experienced diabetes and received any ART before enrollment were excluded from the analysis.We estimated the incidence rate from the number of new onset of HIV-infected adults who had diabetes per Person-Year of Follow-Up (PYFU) and identify the risk factor of diabetes using Cox proportional hazard which included time-updated variables in the model. The variables considered for this analysis included (1) characteristics and laboratory measurement results at ART initiation (i.e. gender, age, body mass index (BMI), HIV RNA, hepatitis B surface antigen, hepatitis C antibody, triglyceride, total cholesterol and calendar year of enrollment), (2) ART regimen which HIV infected adults received at least 5%, and (3) time-updated variables (i.e. BMI, CD4, cumulative duration of ART exposure) considered at the clinical visit which there were the results of blood glucose. As ART regimen might be switched depend on diagnosis of physicians, we separated the analysis into 3 parts to assess the effect of ART on the occurrence of diabetes in HIV-infected adults. First part, we assessed risk factors of diabetes from study variables at ART initiation and time-updated included CD4 and BMI. Second part, we assessed risk factors of diabetes from ART regimen and cumulative duration of treatment which adjusted for the significant variables in the part one. Third part, we assessed the risk of diabetes from patients who received long-term Nucleoside Reverse Transcriptase Inhibitors (NRTI) based first-line ART (at least 2 years). Of 1,594 HIV-infected adults included in the analysis, 1,218 (76%) patients were female. Median age at ART initiation was 32.5 years (Interquartile range; 28.2-37.7). The number of new cases of diabetes during the study was 53 cases and the total person-year was 10,507 PYFU. The incidence rate of diabetes was 5.0 per 1,000 PYFU which less than other studies in United States of America (47.0 per 1,000 PYFU), Italy (20.6), France (14.1), and Taiwan (13.1). In the first part of analysis, the results of multiple analysis showed that age and triglyceride at ART initiation and time-updated BMI were the risk factors of diabetes in HIV-infected adults. In the second part, after adjusted with age and triglyceride at ART initiation and time-updated BMI, we found that receiving didanosine (ddI) + stavudine (d4T) regimen or zidovudine (ZDV) + lamivudine (3TC) + efavirenz (EFV) regimen and cumulative duration of receiving ZDV at least 1 year were the risk factors of diabetes, while receiving tenofovir (TDF) + 3TC + EFV regimen and cumulative duration of receiving TDF or emtricitabine (FTC) at least 1 year were associated with a decreased risk of diabetes. In the third part, a total of 520 HIV infected patients who received first-line ART at least 2 years, including TDF containing regimen, ZDV containing regimen, d4T containing regimen, and ddI + d4T regimen. We found that patients who received ddI + d4T or ZDV containing regimen had significantly higher risk of diabetes than patients who received TDF containing regimen. The results implied the importance of screening and diagnosis of diabetes before ART initiation. For the patients who exposed risk factors of diabetes (elderly, high triglyceride and BMI), the treatment should be included TDF in the regimen to reduce risk of diabetes in HIV infected adults.